Guidelines for Enhancing the Utilization of Information Technology for Learning Management in Artificial Intelligence Era by School Administrators under the Bang Khun Thian District Office in the Bangkok Metropolitian Administration - Tongmark, Phuwadol; Panjarattanakorn, Darunee (Journal of Graduate MCU KhonKaen Campus, 2026)
The objective of this research were: 1) to study the utilization of information technology for learning management, 2) to compare the teachers’ opinions on the utilization of information technology for learning management, and 3) to explore guidelines for enhancing the utilization of information technology for learning management in the Artificial Intelligence era by school administrators under the Bang Khun Thian District Office in the Bangkok Metropolitian Administration. The sample consisted of 248 teachers selected through stratified random sampling according to school size. The research instrument were a questionnaire with content validity, IOC values between .67-1.00, a reliability value of .82 and a semi-structured interview. The data were analyzed by using frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, and LSD and content analysis. The research findings revealed that: 1) The utilization of information technology for learning management, overall and specific aspects were at the highest level, ranking from the highest to the lowest mean, educational media and technology, learning resources, assessment and evaluation, and instructional management. 2) The comparison of the utilization of information technology for learning management in the Artificial Intelligence era among school administrators revealed that teachers with different ages, educational levels, and work experiences had significantly different opinions regarding its use, with statistical significance at the .01 and .05 levels. However, overall, no significant differences were found based on school size. 3) The guidelines for enhancing the utilization of information technology for learning management in the Artificial Intelligence era include systematically planning, developing, and utilizing digital media based on data from Learning Management Systems, student achievement, and user needs. School administrators should encourage teacher participation, establish working groups in collaboration with academic and technology departments, support the use of interactive and adaptive media, create a centralized media database, and promote resource sharing among schools to enhance efficiency and elevate the quality of learning in the age of artificial intelligence.